Intestinal lipid alterations occur prior to antibody-induced prostaglandin E2 production in a mouse model of ischemia/reperfusion - Sparkes, Byron L.; Archer Slone, Emily E.; Roth, Mary R.; Welti, Ruth; Fleming, Sherry D. (My University, 2013)
Ischemia/reperfusion (IR) induced injury results in significant tissue damage in wild-type, but not antibody-deficient, Rag-1-/- mice. However, Rag-1-/- mice sustain intestinal damage after administration of wild-type antibodies or naturally occurring, specific anti-phospholipid related monoclonal antibodies, suggesting involvement of a lipid antigen. We hypothesized that IR initiates metabolism of cellular lipids, resulting in production of an antigen recognized by anti-phospholipid antibodies. At multiple time points after Sham or IR treatment, lipids extracted from mouse jejunal sections were analyzed by electrospray ionization triple quadrupole mass spectrometry. Within 15 min of reperfusion, IR induced significantly more lysophosphatidylcholine (lysoPC), lysophosphatidylglycerol (lysoPG) and free arachidonic acid (AA) production than Sham treatment. While lysoPC, lysoPG, and free AA levels were similar in C57Bl/6 (wild-type) and Rag-1-/- mice, IR led to Cox-2 activation and prostaglandin E[subscript 2] (PGE[subscript 2]) production in wild-type, but not in the antibody-deficient, Rag-1-/- mice. Administration of wild-type antibodies to Rag-1-/- mice restored PGE[subscript 2] production and intestinal damage. These data indicate that IR-induced intestinal damage requires antibodies for Cox-2 stimulated PGE[subscript 2] production but not for production of lysoPC and free AA.
Keywords: Mass spectrometry; Mice; Mouse; Intestine; Lipidomics